Mejoramiento del proceso de obtención de leche bovina con fines económicos en la finca agua linda (2021)
A proposal was carried out to improve the process of obtaining bovine milk in the Agua Linda farm, to increase the utility. This was done starting from the current process, which was fully standardized and quantified, to later determine all its parameters and variables. With the above, a study of the state of the art was carried out and two possible improvements were analyzed: genetic improvement of the cows currently in milking and improvement of the milking system by implementing the tandem milking modality. Subsequently, four proposals were raised as a mathematical exercise, which were: conventional milking and insemination, conventional milking and buying milk-type cows, tandem-type milking and inseminating, and tandem-type milking and buying milk-type cows, in order to find the more useful way. In the end, it was determined that the tandem-type milking way and the purchase of milk-type cows is the most viable for the farm, taking into account that it presents a total profit in the 10 years of the project equal to 3.605'855.229 COP. With that, it was possible to demonstrate that the modernization of agro-industrial systems and genetic improvement are a profitable alternative and that they can make Colombian livestock a competitive economic sector at a national and international level.